Visual Research Methods: A Novel Approach To Understanding The Experiences of Compulsive Hoarders: A Preliminary Study - Satwant Singh; Colin Jones (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Compulsive hoarding is a syndrome characterised by excessive collecting and saving behaviour that results in cluttered living space and significant distress or impairment. This study set out to gain a greater understanding of the personal experiences of compulsive hoarders in addition to attaining their evaluations of attending a therapy group. Method: Using a participatory photography methodology, a purposive sample of 12 members of a hoarding therapy group were recruited. Participants were asked to take photographs which best captured their hoarding problems. The photographs were then used to encourage narrative dialogue in a subsequent semi structured interview. Results: Seven key themes emerged from the data including: Feelings of isolation and vulnerability, lifestyle disruption, losing and misplacing, clutter and metaphor, rationalisation of the acquisition of hoarded items, failed previous support and the benefits of a therapy support group. Conclusion: The study concluded that the experience of hoarding is both psychologically and physically distressing with numerous impacts upon everyday living and relationships. The study also concluded that visual research methods may be particularly helpful when generating qualitative evidence within this specialist field.